Japanese Quince Chaenomeles Japonica (Thunb.) Lindl. ex Spach Leaves a New Source of Antioxidants for Food. Issue 1 (1st January 2019) - Urbanaviciute, Ieva; Liaudanskas, Mindaugas; Seglina, Dalija; Viskelis, Pranas
ABSTRACT: Japanese quince ( Chaenomeles japonica (Thunb.)) is a very important ornamental plant that is rich in many biochemical compounds such as antioxidants and secondary metabolites that have positive effects on human health. The aim of the study was to evaluate the biochemical compounds in the leaves of three Japanese quince ( Chaenomeles japonica (Thunb.)) Lindl. ex Spach cultivars (ʻRasaʼ, ʻDariusʼ and ʻRondoʼ). The results showed that the leaves of Japanese quince have strong antiradical activity (1091 ± 22–1135 ± 15 µmol TE/g) in the CUPRAC reaction system. The analysis by the HPLC method revealed that the major polyphenol group in Japanese quince cultivars leaves was phenolic acids and the most common polyphenol compound is chlorogenic acid (11.2– 52.4 mg/g DW). The most common triterpene is ursolic acid (3.7– 6.8 mg/g DW). Japanese quince leaf powder can be used as a food or beverage additive and enriches our diet with compounds with strong antioxidant activity.